2010
DOI: 10.1515/znb-2010-0607
|View full text |Cite
|
Sign up to set email alerts
|

π-Spacer-coupled Diimidosulfinates

Abstract: To synthesize ligands that are capable of coordinating two metals, 1,4-dilithiumbenzene and 4,4 -dilithiumbiphenyl were reacted with different sulfurdiimides to give coupled diimidosulfinates.[ (THF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Dibromobenzene (Fig.5top left), 4,4-dibromobiphenyl (Fig.5top right)34 and 9,10-dibromoanthracene35 are suitable linkers for two moieties. If 9,10-dibromoanthracene is only lithiated at one of the two positions with nBuLi and reacted with sulfur diimide the reactions proceed smoothly and afford [(thf) 2 Li(NtBu) 2 SAnBr] and [Me 2 Al(NtBu) 2 SAnBr] in a transmetalation reaction with Me 2 AlCl (An = anthracenyl, C 14 H 8 , Fig.5bottom left).…”
mentioning
confidence: 99%
“…Dibromobenzene (Fig.5top left), 4,4-dibromobiphenyl (Fig.5top right)34 and 9,10-dibromoanthracene35 are suitable linkers for two moieties. If 9,10-dibromoanthracene is only lithiated at one of the two positions with nBuLi and reacted with sulfur diimide the reactions proceed smoothly and afford [(thf) 2 Li(NtBu) 2 SAnBr] and [Me 2 Al(NtBu) 2 SAnBr] in a transmetalation reaction with Me 2 AlCl (An = anthracenyl, C 14 H 8 , Fig.5bottom left).…”
mentioning
confidence: 99%
“…In the reaction with Me 2 AlCl both lithium atoms are exchanged by aluminum resulting in a bimetallic symmetrical complex rather than in a heterobimetallic species. This phenomenon was already observed when benzene and biphenyl spacers were employed [20]. It seems that Me 2 AlCl is too reactive and not selective enough to exchange just one lithium atom by salt elimination.…”
Section: Synthesis Of [{(Thf) 2 Li(nr)mentioning
confidence: 85%
“…Since [(THF) 4 Li 2 {(NSiMe 3 ) 2 S} 2 biphenyl] also crystallizes as a monomer [20], it is anticipated that one reason for this uncommon structural motif is the aryl group connected to the sulfur atom. The biphenyl and the anthracene substituent both can form C-H··· π hydrogen bonds.…”
Section: Sanbr] (3) (An = Anthracenyl C 14 H 8 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Stalke et al successfully applied this particular synthetic approach also for the synthesis of Janus-type multidentate ligands as well as spacer-bridged bis­(diimidosulfinates). , In addition to the well-known alkali metal and alkaline earth metal diimidosulfinates [RS­(NR′) 2 ]­[M­(solv)] [M = Li, Na, K, Rb, Cs; MgX], which are accessible either by treating sulfurdiimides with different Grignard reagents or by reaction of N , N ′-bis­(trimethylsilyl)-aminoiminphenylsulphine PhS­(NSiMe 3 )­N­(H)­SiMe 3 with bis­(trimethylsilyl)­amides [M­{(N­(SiMe 3 ) 2 }] (M = Ca, Sr, Ba), , several experimental studies on the synthesis of other main group and transition metal diimidosulfinates complexes have been reported. They are almost exclusively synthesized by reaction of the alkali metal diimidosulfinates with the corresponding metal halides or amides. , Moreover, simple Lewis acid–base adducts of sulfurdiimide with several metal halides such as TiCl 4 , GaCl 3 , and SnCl 4 , respectively, have been synthesized, while Weidlein et al reported on insertion reactions of bis­(trimethylsilyl)­sulfurdiimide with trimethylalane, -gallane, and -indane MMe 3 (M = Al, Ga, In) . In contrast, reactions of S­(NSiMe 3 ) 2 with either a zirconium imide or the titanocene alkyne complex [Cp 2 Ti­(η 2 -Me 3 SiC 2 SiMe 3 )] yielded titanium trisimidosulfite complexes in a rather complex reaction mechanism, , while the analogous reaction with [Cp 2 Ti­(η 2 -Me 3 SiC 2 SiMe 3 )] gave an unusual four-membered metallacycle …”
Section: Introductionmentioning
confidence: 99%